Financial Risk Mitigation Through Sustainability: Evidence from Construction Sector in Southeast Asia - Rustandi Rustandi; Tri Gunarsih; Nuryasman Nuryasman; Faizul Mubarok (Politeknik Siber Cerdika Internasional, 2026)
Background: The construction sector is highly exposed to financial risk due to cost overruns, delayed payments, and market volatility. However, limited studies have examined how multidimensional financial risks affect firm value in Southeast Asia, particularly when ESG is positioned as a risk-mitigation mechanism. Objective: This study examines the effects of bankruptcy risk, fundamental risk, and liquidity risk on firm value while testing the moderating role of ESG in construction firms across Southeast Asia from 2015 to 2024. Methods: This study employed an explanatory quantitative design using unbalanced panel data, consisting of 1,831 observations for the direct risk model and 240 observations for the ESG moderation model. The data were analyzed using static panel estimation with Driscoll–Kraay standard errors and dynamic System GMM estimation. Results: Bankruptcy risk, fundamental risk, and liquidity risk significantly affected firm value across different model specifications. ESG significantly moderated the relationship between bankruptcy risk and firm value, indicating that sustainability practices strengthen the market signal of financial stability. However, ESG did not significantly moderate the effects of fundamental risk or liquidity risk on firm value. Conclusion: ESG practices selectively enhance firm resilience against bankruptcy risk, whereas operational and liquidity risks are assessed more independently by the market. This study contributes cross-country evidence on financial risk, firm value, and sustainability in Southeast Asia’s construction sector.